Homocitrate synthase connects amino acid metabolism to chromatin functions through Esa1 and DNA damage - Scott, Erin M. (Cold Spring Harbor Laboratory Press, 2010)
The enzyme homocitrate synthase (HCS) catalyzes the first step in lysine biosynthesis, and early biochemical data placed it in the cytoplasm or mitochondria, where most amino acid synthesis occurs. It was therefore surprising when refined fractionation techniques and specific immunoreagents clearly demonstrated its localization to the nucleus. These observations raised the question of whether HCS had a function within the nucleus independent of lysine synthesis. We demonstrate that HCS encoded by LYS20 in yeast is linked to the key process of DNA damage repair through the essential MYST family histone acetyltransferase Esa1 and the H2A.Z histone variant. This discovery indicates that HCS has a role in addition to amino acid synthesis, and that it functions in nuclear activities involving chromatin regulation that are distinct from its previously established role in lysine biosynthesis. The chromatin-linked roles are dependent on nuclear localization of Lys20, but are independent of HCS catalytic activity. Thus, Lys20 appears to have evolved as a bifunctional protein that connects cellular metabolism with chromatin functions.